Principles and methods for assessing direct inmunotoxicity associated with exposure to chemicalsImmunotoxicity associated with exposure to chemicals, principles and methods for assessment (Environmental health criteria)
El texto completo se encuentra disponible en la página: http://www.inchem.org/pages/ehc.html